Transition out of sport and role adjustment : a comparative case study of past and present national track and field athletes of Malaysia - Kavitha Subaramaniam (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2010)
Transition out of sport is rarely studied in Malaysia because not many researchers prefer to look into the post-sport events. Generally, nobody knows what had happened to these retired athletes after they disengage from sport domain. The aim of this research is to explore the process of transition out of sport for the track and field athletes and their adjustment in the new situations. Second, to study how former athletes' adopt new roles in society after retiring from sport. Third, assessing the impact of their previous identity as sportsperson in their current role. Case study method was applied to study the problem because it explored the former athletes' experiences and provided detailed information about their role. As such in-depth interviews with open-ended questions were conducted to understand their transition process in facing their new role in society. However, the first five case studies consisted of the past generation athletes who stopped their active participation from sports by the mid 1970s. Their involvement in sports was only as hobby and recreation as sport was not a full-fledged career. The other five case studies looked into the present generation athletes who retired by mid 2000s. They however, were privileged to have sport as profession because the National Sports Council Malaysia (NSC) introduced a full-time training programme. The two different timelines was chosen in order to assess the difference in transition and role adjustment process that these former athletes have gone through. The findings of this study had concluded that the former track and field national athletes from the past and present generations in Malaysia had navigated smoothly in their transition out of sport and had adjusted their lives after sport with least trauma where it did not reflect the typical findings that usually associated with negative experiences.